DISCIPLINE AS A CONTROLLING FACTOR IN THE LEARNING OF AN-NUR 2 AL-MURTADLO MALANG SANTRI - Hazmy, Ahmad Mu'adz Hazmy Sastria; Pardiman; Djony Harijanto (Pena Cendekia Insani, 2025)
Islamic boarding schools are non-formal educational institutions that are essential in shaping the character of students through discipline, which is vital for the effectiveness of learning. This study investigates the mediating role of santri discipline in controlling learning at An-Nur 2 Al-Murtadlo Islamic Boarding School in Malang. Using a descriptive qualitative approach and a single case study, data were collected through observation, in-depth interviews with key informants and santri, and documentation. Data analysis was carried out by reduction, presentation, and verification, supported by source triangulation. The results showed that santri discipline has a strategic role as a link in controlling learning. Discipline is formed from daily habituation, adherence to rules, and exemplary management. Systematic learning planning contributes to a disciplined environment. Control through supervision and coaching encourages orderly and responsible behavior. Strengthening discipline through educational rewards and punishments has proven effective. Thus, diniyah discipline is not only the result, but also the main driver for the achievement of effective and meaningful pesantren education goals.